Dermatofibrosarcoma protuberans (DFSP) in children: A combined multidisciplinary approach. Issue 1 (11th November 2020) - Sleiwah, Aseel; Psomadakis, Cristina; Craythorne, Emma; Stefanato, Catherine M.; Rickaby, William; Robson, Alistair; Mellerio, Jemima E.; Greig, Aina
Abstract: Dermatofibrosarcoma protuberans (DFSP) is rare, comprising (1%‐6%) of all sarcomas. The incidence is less than one per million before the age of 20. It is a locally aggressive tumor with a low risk of metastasis. We share our experience in the management of three pediatric patients with complex cases of DFSP in a combined surgical approach involving plastic and dermatologic surgery, using the slow Mohs micrographic surgery technique.